2021
DOI: 10.3390/coatings11010084
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Chitosan Films Incorporated with Different Substances of Konjac Glucomannan, Cassava Starch, Maltodextrin and Gelatin, and Application in Mongolian Cheese Packaging

Abstract: Four kinds of edible composite films based on chitosan combined with additional substances (konjac glucomannan, cassava starch, maltodextrin and gelatin) and the addition of lysozyme were prepared and used as packaging materials for Mongolian cheese. The prepared composite films were evaluated using scanning electron microscopy and Fourier transform infrared spectroscopy. The physicochemical properties of all chitosan composite films, including thickness, viscosity, opacity, color, moisture content, water vapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…Similar results were reported regarding the thickness of the films prepared by combining gelatin and starch (Ma et al, 2021), those made of soy protein, starch, and maltodextrin (Galus et al, 2012), and kappa-carrageenan films with a savory essence (Shojaee-Aliabadi et al, 2013), indicating appropriate compatibility between film components. The studies as mentioned earlier indicated that the difference in the thickness of the films depends on the preparation method and the amount of additive.…”
Section: Thicknesssupporting
confidence: 85%
“…Similar results were reported regarding the thickness of the films prepared by combining gelatin and starch (Ma et al, 2021), those made of soy protein, starch, and maltodextrin (Galus et al, 2012), and kappa-carrageenan films with a savory essence (Shojaee-Aliabadi et al, 2013), indicating appropriate compatibility between film components. The studies as mentioned earlier indicated that the difference in the thickness of the films depends on the preparation method and the amount of additive.…”
Section: Thicknesssupporting
confidence: 85%
“…
As a traditional fermented dairy food in Inner Mongolia, Mongolian cheese has become an indispensable part of consumers' tables because of its rich nutrition and unique taste (Ma et al, 2021). However, it has been found that cheese is easily contaminated by pathogenic microorganisms during processing, packaging, transportation, and storage (Ahmed et al, 2021).
…”
mentioning
confidence: 99%
“…Additionally, a bacteriostatic agent is used in packaging. This has the potential to expand the antimicrobial spectrum, enhancing antibacterial activity, and reducing the impact on the sensory properties of cheese products. New lysozyme-based antibacterial reagents or packaging materials can be created by combining lysozyme with antifungal medicines or active chemicals, particularly those that target Penicillium spp. As a result, it not only aids in the precise and multifaceted control of bacteria and molds but also provides new avenues for the prevention and control of mycotoxin contamination in cheese products during maturation.…”
Section: Control Of Cit Contamination In Cheese Productsmentioning
confidence: 99%